24: IDEAL IMPLEMENTATION OF THE MINIMALLY INVASIVE CERVICAL ESOPHAGECTOMY (MICE), A JAPANESE-DUTCH COLLABORATION. (23rd April 2022) - Klarenbeek, B; Shiozaki, A; Fujiwara, H; Rosman, C
Abstract: Background and aim: MICE is an innovative Japanese surgical technique, combining a laparoscopic transhiatal and a single port cervical mediastinal dissection in patients operated for esophageal cancer. This complex surgical techniques aims to reduce pulmonary morbidity without compromising oncological radicality by avoiding thoracic access, prevailing pleural integrity and facilitating cervical or abdominal instead of pleural drainage of mediastinal infections in case of anastomotic leakage. Potential drawbacks are an increased risk of recurrent laryngeal nerve injury and learning associated morbidity during the implementation phase. Up to date this technique is not routinely performed in European esophageal cancer patients. Methods: In order to explore the feasibility and safe implementation of the MICE procedure in Dutch esophageal cancer patients, the evidence based IDEAL-framework will be followed. This framework describes 6 stages of evolution for new surgical therapeutic interventions: Pre-clinical, First in human, Development, Exploration, Assessment and Long-term Study. Outcomes of the first two phases will be described. Results: The Pre-clinical phase consisted of on-site visits to a Japanese expert center, protocol development, prospective risk assessment, instrument collection and extensive cadaveric training on six fresh frozen human bodies. A 'virtual supervision platform' has been developed to proceed with the implementation process despite the COVID pandemic. After thorough evaluation with Dutch upper GI surgical experts and esophageal cancer patients, we have proceeded to the 'First in Human' phase. Conclusion: The IDEAL framework was used as an evidence based tool for safe implementation of the MICE procedure. We will present the results of the 'pre-clinical' and 'first in human' stage as well as the surgical technique of the MICE procedure.